2006
DOI: 10.1631/jzus.2006.b0038
|View full text |Cite
|
Sign up to set email alerts
|

Study on NO2 absorption by ascorbic acid and various chemicals

Abstract: Study on NO 2 absorption aimed at seeking a better NO 2 absorption chemical at pH 4.5~7.0 for application to existing wet flue gas desulfurization (FGD). The results from the double-stirred reactor indicated that ascorbic acid has very high absorption rate at this pH range. The rate constant of ascorbic acid reaction with NO 2 (0~1000×10 −6 mol/mol) is about 3.54×10 6 mol/(L⋅s) at pH 5.4~6.5 at 55 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…For a given energy density of around 1000 J/L, the NO x removal (NO oxidation) efficiencies are 90.2% (100%), 87% (97%), and 80% (91%) at pH of 7.5, 4, and 2, respectively. This is because the ratio of SO 3 2– conversion to HSO 3 – increases with the decrease of pH, and the reaction rate constant of NO 2 and SO 3 2– (1.12 × 10 6 mol/(L·s)) is 2 orders of magnitude larger than that of NO 2 and HSO 3 – (2.8 × 10 4 mol/(L·s)) …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a given energy density of around 1000 J/L, the NO x removal (NO oxidation) efficiencies are 90.2% (100%), 87% (97%), and 80% (91%) at pH of 7.5, 4, and 2, respectively. This is because the ratio of SO 3 2– conversion to HSO 3 – increases with the decrease of pH, and the reaction rate constant of NO 2 and SO 3 2– (1.12 × 10 6 mol/(L·s)) is 2 orders of magnitude larger than that of NO 2 and HSO 3 – (2.8 × 10 4 mol/(L·s)) …”
Section: Results and Discussionmentioning
confidence: 99%
“…This is because the ratio of SO 3 2− conversion to HSO 3 − increases with the decrease of pH, and the reaction rate constant of NO 2 and SO 3 2− (1.12 × 10 6 mol/(L•s)) is 2 orders of magnitude larger than that of NO 2 and HSO 3 − (2.8 × 10 4 mol/(L•s)). 16 However, the accumulated NO 2 − produced via eq R16 in the mist may be decomposed according to a disproportionation reaction as follows: 1…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…In some similar studies reported in the literature, the values of Ha are similar to those observed in this work. 27,36 However, the values of overall rate constant with various oxidants were evaluated by the principle of Danckwert's theory by Li et al 37 The overall order of reaction was reported as 1, whereas the overall rate constant was of the order of 10−6 mol•L −1 •s −1 at pH 5.4−6.5 at 328 K. The current study can be utilized for calculation of the kinetics and mass transfer parameters for the bubble column reactor. It was observed that the peroxone process is more efficient for the absorption of NO 2 at a wide range of pH and temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The double-stirred reactor had a gas-liquid interface that was planar to a close approximation (22,23). The reactor was 61 mm in diameter and equipped with four vertical baffles and two stirring blades.…”
Section: Experiments On Toluene Absorptionmentioning
confidence: 99%